BODIPY-based polymeric dyes as emerging horizon materials for biological sensing and organic electronic applications. (August 2017) - Squeo, Benedetta M.; Gregoriou, Vasilis G.; Avgeropoulos, Apostolos; Baysec, Sebnem; Allard, Sybille; Scherf, Ullrich; Chochos, Christos L.
Abstract: The design, synthesis, and characterization of BODIPY (4, 4′-difluoro-4-bora-3a, 4a-diaza-s-indacene)-based small molecules has undergone tremendous progress in the past two decades. BODIPYs and their dipyrrin precursors have been recently reviewed with emphasis placed on their syntheses, reactions and applications including biochemical labelling, fluorescent switches, chemosensors, and electroluminescent devices. Compared to other dye classes, these systems offer unique attractions such as excellent thermal/photochemical stability, intense absorption/emission profiles, negligible triplet-state formation, and small Stokes shifts. Their optoelectronic and semiconductor properties can be finely tuned via facile synthetic modifications on the dipyrromethene core, while their optical characteristics are relatively insensitive to medium polarity and the pH of the environment. On the contrary, the optoelectronic and photophysical properties of BODIPY-based polymeric semiconductors the newest developed family in BODIPY-based organic materials (the first BODIPY based conjugated polymers were published in 2008) are still not well understood. For fully resolving these open questions, it will be shown in this review that the optoelectronic and photophysical properties of the BODIPY-based conjugated polymers are depending on various parameters including: (i) the positions where the BODIPY core will be attached into the polymer backbone (α-, β-, meso positions, or fluorine substitution) and (ii) the number of methyl substituents on 1, 2, 3, 5, 6, and 7 positions and finally (iii) if BODIPY functions as electron rich or electron deficient building block in "donor-acceptor" (D-A) conjugated polymers. This is a very significant advance in the emerging field of BODIPY chemistry since it opens the path for further optimization of the recent and new developed BODIPY-based polymeric semiconductors with predetermined optoelectronic and photophysical properties by providing new design rules to organic and material chemists as well as physical (bio)chemistry and device (bio)engineering scientists.